High-sulfur-resistance wide-temperature window denitration catalyst as well as preparation method and application thereof
By combining modified TiO2-based support and rare earth metal oxides, a high-sulfur-resistant wide-temperature window denitrition catalyst with porous structures is designed, which solves the problem of failure of traditional catalysts under low temperature conditions, and achieves efficient denitrification and anti-ammonium bisulfate deposition, reducing the deposition of high-efficiency Operating costs and NOx emissions.
Patent Information
- Application Number
- CN202310694110.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-13
AI Technical Summary
The traditional catalysts used for flue gas denitrition in existing coal-fired power plants fail under low temperature conditions, resulting in increased NOx emissions, shortened catalyst life, high operating costs, and insufficient sulfur resistance, making it difficult to meet strict environmental protection requirements.
Develop a high sulfur-resistant wide temperature window denitrogenation catalyst, using modified TiO2-based support combined with rare earth metal oxides and oxide components such as vanadium, molybdenum, antimony, niobium, etc., to improve the catalyst through acid modification treatment and porous structure design and its ability to resist ammonium bisulfate deposition.
The catalyst maintains high activity under a wide temperature window, reduces SO2 oxidation rate, extends service life, and reduces production costs. It can achieve efficient denitrification in the range of 180-420℃, and is suitable for complex flue gas conditions.
Smart Images

Figure CN119114053A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of denitration catalysts, and in particular, to a high-sulfur-resistant and wide-temperature-window denitration catalyst, and a preparation method and application thereof. Background Art
[0002] Nitrogen oxides (NO x ) is one of the main atmospheric pollutants, an important factor in the formation of acid rain, one of the important precursors for the formation of ozone and photochemical smog, and an important cause of regional ultrafine particle (PM2.5) pollution and haze.
[0003] Coal-fired power plants are NO x One of the main sources of emissions. Traditional commercial V2O5 / WO3-TiO2 catalysts are commonly used in flue gas denitrification in coal-fired power plants, and their optimal active temperature range is 300-420℃. In recent years, due to the improvement of environmental protection requirements, strict requirements for the emission of nitrogen oxides from the start-up and shutdown of furnaces, and the demand for deep peak regulation of thermal power, more than 60% of coal-fired units are in low-load operation, and the flue gas temperature is often lower than 300℃; when the flue gas temperature is lower than the optimal ammonia injection temperature, power plants generally increase the amount of ammonia injection to improve the denitrification efficiency to varying degrees, resulting in increased operating costs, excessive ammonia escape, shortened catalyst life, and frequent blockage of air preheaters, which brings new problems and challenges to the safe operation of the units. The current solution to this problem is to reduce the heat intake of the economizer before the denitrification system through engineering transformation, so that the inlet flue gas temperature of the denitrification system under low load (<50% THA) reaches above 300℃ so that the traditional catalyst can operate normally, including split economizer, flue gas bypass, economizer water side bypass, economizer hot water recirculation, etc. However, these methods are expensive to transform, have a long construction period, reduce boiler efficiency, increase power plant operating costs, and significantly increase power plant losses. Wide-temperature denitration catalysts can expand the operating temperature window to 240-420°C, effectively reducing the minimum ammonia injection temperature range of denitration catalysts without changing the overall structure and system of the boiler, and achieving the national ultra-low emission environmental protection requirements for nitrogen oxide emissions under unit start-up and shutdown and low-load conditions. The transformation cost is only the normal replacement of the catalyst, which has significant economic benefits.
[0004] Coal accounts for 70% of my country's energy structure. Unlike Western countries, my country's coal quality generally has the characteristics of high sulfur and high ash. Under the condition that the unit operation is not precise and reasonable, the denitrification catalyst faces serious failure problems during use. Specifically, the combustion conditions are unstable during the start-up and shutdown of the unit and the deep peak regulation, so the NO inlet of the denitrification system is xThe concentration is 2 to 3 times higher than that in stable operation, which also poses a severe test to the denitration efficiency of the catalyst. Under boiler combustion conditions, about 1% of SO2 is converted into SO3, and another 1% of SO2 is converted into SO3 when passing through the denitration system. This is combined with the injected reducing agent NH3 and the water in the flue gas to form ammonium bisulfate (ABS). When the flue gas temperature is lower than 300°C, it will condense into a viscous substance, causing the micropores of the catalyst to be blocked, covering the active sites and causing the catalyst to be deactivated. Secondly, SO3 will also react chemically with V2O5 in the catalyst to generate VOSO4, causing the catalyst to slowly deactivate. The dew point temperature of ammonium bisulfate (ABS) is related to the concentration product of SO3, H2O and NH3 in the flue gas. According to the design conditions of different projects, it is generally in the range of 280-300°C. The higher the SO2 concentration in the flue gas, the higher the oxidation rate of the catalyst to SO2, the larger the corresponding [SO3]·[H2O]·[NH3] concentration product, the higher the ABS dew point temperature, and the greater the risk of failure of the catalyst in low-temperature operation. At present, the commonly used method to resist ABS poisoning in industrial flue gas denitrification is to heat the catalyst temperature to above the dew point temperature of ABS. However, the load changes of coal-fired power plants need to change according to the changes in the power grid, and it is difficult to provide such an operating environment. Therefore, the development of low-SO2 oxidation rate, ABS-poisoning-resistant low-temperature NH3-SCR denitrification technology has great scientific significance and practical value in the fields of environment and energy, and is also a difficulty in current industry technology. Summary of the invention
[0005] The purpose of the present disclosure is to provide a high sulfur resistance and wide temperature window denitrification catalyst and its preparation method and application. The catalyst prepared by the method can reduce the oxidation rate of SO2, the catalyst has high activity, is resistant to ammonium bisulfate deposition failure at low temperature, and has low cost.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present disclosure provides a high sulfur resistance and wide temperature window denitrification catalyst, the catalyst having an acidic site, the catalyst comprising a modified TiO2-based carrier, a first active component and a second active component, the first active component and the second active component being distributed on the outer surface of the modified TiO2-based carrier; the first active component comprising an oxide of a rare earth metal element, and the second active component being selected from one or more of the oxides of vanadium, molybdenum, antimony, niobium and tin; based on the dry weight of the catalyst, the content of the modified TiO2-based carrier is 91.0 to 96.0% by weight, the content of the oxide of the first active component is 3.0 to 6.0% by weight, and the content of the oxide of the second active component is 1.0 to 3.0% by weight;
[0007] Among them, the content of the modified TiO2-based carrier is calculated as the amount of TiO2, the content of the first active component is calculated as the total amount of rare earth metal element oxides, and the content of the second active component is calculated as the total amount of vanadium, molybdenum, antimony, niobium and tin element oxides.
[0008] Optionally, the outer surface of the modified TiO2-based carrier is coated with a first active component layer and a second active component layer in sequence; the modified TiO2-based carrier is a TiO2-based carrier modified by an acid modifier; the modified TiO2-based carrier contains TiO2, and optionally WO3 and / or SiO2; the acid modifier is selected from organic acid and / or inorganic acid.
[0009] Optionally, the modified TiO2-based carrier is a porous material, and the porous material contains macropores, mesopores and micropores; the specific surface area of the modified TiO2-based carrier is 50 to 90 m 2 / g, preferably 60 to 90 m 2 / g; pore volume is 0.3~0.6cm 3 / g, preferably 0.4 to 0.5 cm 3 / g; the pore volume of the macropores accounts for 2-10% of the pore volume of the porous material; the pore volume of the mesopores accounts for 30-50% of the pore volume of the porous material, and the pore volume of the micropores accounts for 45-75% of the pore volume of the porous material.
[0010] Optionally, the rare earth metal element is selected from one or more of cerium, lanthanum, praseodymium, erbium and samarium.
[0011] The second aspect of the present disclosure provides a method for preparing the catalyst according to the first aspect, the method comprising the following steps:
[0012] S1, mixing a TiO2-based carrier, an acid modifier and water and performing a modification treatment at 60-80° C., and performing a first drying and a first calcination on the product after evaporation to obtain a first material;
[0013] S2, performing a second mixing, a second extrusion, a second drying and a second calcination on the first material and the molding aid to obtain a modified TiO2-based carrier;
[0014] S3, performing a third impregnation of the modified TiO2-based carrier in the first auxiliary agent, and performing a third drying of the modified TiO2-based carrier after the third impregnation to obtain a third material;
[0015] S4, performing a fourth impregnation of the third material in the second auxiliary agent, and performing a fourth drying and a fourth calcination of the third material after the fourth impregnation;
[0016] Wherein, the first auxiliary agent comprises a first active component source, and the second auxiliary agent comprises a second active component source.
[0017] Optionally, in step S1, the TiO2-based carrier is selected from one or more of titanium dioxide, titanium tungsten powder and titanium tungsten silicon powder; the concentration of the acid modifier is 0.05-1.2 mol / L, preferably 0.5-1.0 mol / L; the acid modifier is selected from organic acid and / or inorganic acid; the mass ratio of the TiO2-based carrier to the acid modifier is 1:(10-30); in step S2, the molding aids include: a lubricant, a reinforcing agent, a pore former, a binder and a pH regulator; the lubricant is selected from one or more of stearic acid, lactic acid and glycerol; the reinforcing agent is selected from glass fiber and / or lignin; the pore former is selected from one or more of pulp cotton, activated carbon and sesbania powder; the binder is selected from one or more of hydroxymethyl cellulose, polyvinyl alcohol and polyethylene oxide; the pH regulator is ammonia water, and the mass concentration of NH3 in the ammonia water is ≥20%;
[0018] In step S3, the first auxiliary agent is a soluble salt containing a first active component source, the first active component source contains a rare earth element, the first active component source is selected from one or more of a vanadium source, a molybdenum source, an antimony source, a niobium source and a tin source, preferably selected from one or more of cerium nitrate, lanthanum nitrate, praseodymium nitrate, samarium nitrate and erbium nitrate;
[0019] In step S4, the second auxiliary agent is a mixture containing a second active component source, and the second active component source is selected from one or more of a molybdenum source, an antimony source, a niobium source and a tin source, preferably selected from one or more of ammonium heptamolybdate, antimony acetate, niobium oxalate, ammonium niobium oxalate and tin acetate.
[0020] Optionally, the organic acid is selected from monobasic organic acid and / or dibasic organic acid, preferably oxalic acid and / or acetic acid; the inorganic acid is selected from tribasic inorganic acid, preferably phosphoric acid; the concentration of the first auxiliary agent is 0.1-4.0% by weight, preferably 0.2-1.5% by weight; the second auxiliary agent also contains a cosolvent and a second auxiliary compound, and the mass ratio of the cosolvent, the second active component source and the second auxiliary compound is (0.5-0.8): (0.2-1.8): 1, preferably (0.6-0.7): (0.5-1): 1.
[0021] Optionally, in step S1, the first drying conditions include: temperature of 80 to 120° C. and time of 12 to 24 hours;
[0022] The first calcination conditions include: a temperature of 200 to 300° C. and a time of 8 to 20 hours;
[0023] In step S2, the second drying conditions include: temperature of 60-80°C, time of 12-15 days, and humidity of 40-60%;
[0024] The second calcination conditions include: a temperature of 200 to 300° C. and a time of 20 to 30 hours;
[0025] In step S3, the temperature of the third immersion is 10-30°C, preferably 15-25°C; the time is 7-15 minutes, preferably 10-13 minutes;
[0026] The conditions of the third drying include: a temperature of 60 to 90°C, preferably 70 to 80°C; a time of 12 to 20 hours, preferably 14 to 18 hours;
[0027] In step S4, the temperature of the fourth dipping is 60-80°C, preferably 60-70°C; the time is 5-12 minutes, preferably 8-10 minutes;
[0028] The fourth drying conditions include: temperature of 60-90°C, preferably 70-80°C; time of 15-30h, preferably 20-24h; humidity of 40-60%, preferably 45-55%;
[0029] The conditions for the fourth calcination include: a temperature of 500 to 600° C., preferably 500 to 550° C.; and a time of 30 to 50 hours, preferably 35 to 45 hours.
[0030] The third aspect of the present disclosure provides application of the catalyst described in the first aspect in flue gas denitrification.
[0031] Optionally, the method comprises the following steps: at 200 to 420°C, heating the flue gas for 3000 to 8000 hours -1 The flue gas is passed into a stainless steel fixed bed reactor containing the catalyst at a space velocity to contact the catalyst; the concentration of SO2 in the flue gas is 3000-6000 mg / m 3 The concentration of nitrogen oxides is 300-500 ppm, the concentration of NH3 is 300-500 ppm, the volume concentration of O2 is 3-5%, and the volume concentration of water vapor is 8-15%.
[0032] Through the above technical scheme, the present disclosure provides a high sulfur resistance and wide temperature window denitration catalyst and its preparation method and application. The catalyst prepared by this method has the following advantages:
[0033] (1) The acid-modified carrier increases the acidic sites on the carrier surface, which is beneficial to improving the basic activity of the porous catalyst; the addition of rare earth metal elements increases the oxygen vacancies on the catalyst surface, which is beneficial to the conversion of NO to NO3 at low temperatures - transformation.
[0034] (2) The porous material is first extruded, and then the first auxiliary agent and the second auxiliary agent are impregnated step by step, so that the active components are distributed more on the catalyst surface, avoiding the active components from being distributed in the SO2 oxidation zone to produce side reactions and waste active components, reducing the SO2 oxidation rate and saving the catalyst production cost.
[0035] (3) The added second active component can promote the volatilization of ammonium bisulfate and inhibit the deposition of ammonium bisulfate, making the catalyst less likely to be poisoned and deactivated, thereby increasing the service life of the catalyst.
[0036] (4) The carrier adopts a porous composite. The macropores promote the volatilization of ABS deposited in the pores, and the mesoporous carrier realizes good dispersion of the active components of the catalyst, which can reduce the side reaction SO2 oxidation reaction and ammonium bisulfate deposition rate, and effectively slow down the catalyst deactivation.
[0037] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The accompanying drawings are used to provide further understanding of the present disclosure and constitute a part of the specification. They are used to explain the present disclosure together with the following detailed description, but do not constitute a limitation of the present disclosure.
[0039] In the attached picture:
[0040] Figure 1 NH3-TPD curves of Example 1 and Comparative Example 1 in the present disclosure. DETAILED DESCRIPTION
[0041] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0042] The first aspect of the present disclosure provides a high sulfur resistance and wide temperature window denitrification catalyst, which has an acidic site. The catalyst contains a modified TiO2-based carrier, a first active component and a second active component, and the first active component and the second active component are distributed on the outer surface of the modified TiO2-based carrier.
[0043] In the present disclosure, the first active component is distributed on the surface outside the modified TiO2-based carrier, which can achieve physical separation of the catalyst denitration zone and the SO2 oxidation zone, and significantly reduce the amount of active components under the premise of reducing the denitration efficiency, thereby reducing the SO2 / SO3 oxidation rate; the second active component is distributed on the surface of the first active component layer, which can further inhibit the adsorption of SO3 on the catalyst surface, improve the catalyst's resistance to ammonium bisulfate at low temperature and its volatilization rate in the catalyst pores, so that the catalyst can obtain high activity and high sulfur resistance in a wide temperature window. The first active component and the second active component are distributed in the 0-200μm area of the outer surface of the modified TiO2-based carrier, which can effectively improve the denitration reaction of the catalyst on the one hand, and reduce the SO2 / SO3 conversion rate on the other hand.
[0044] In a preferred embodiment of the present disclosure, a first active component layer and a second active component layer are sequentially coated along the outer surface of the modified TiO2-based carrier. The catalyst disclosed in the present disclosure sequentially loads the first active component layer and the second active component layer on the surface of the porous material modified TiO2-based carrier, which can reduce the deposition rate of the side reaction SO2 oxidation reaction and ammonium bisulfate (ABS), and effectively slow down the deactivation of the catalyst; and the catalyst has high activity at low temperatures, a wide temperature window, and strong adaptability to complex flue gas components, in the temperature range of 180 to 420°C, preferably 200 to 380°C, and an air velocity of 3000 to 8000 h -1 , catalyst is 3000~6000mg / m 3 Under high SO2 concentration, the denitrification efficiency exceeds 90%.
[0045] In a specific embodiment of the present disclosure, the first active component contains an oxide of a rare earth metal element, and the second active component is selected from one or more oxides of vanadium, molybdenum, antimony, niobium and tin.
[0046] In a preferred embodiment of the present disclosure, the rare earth metal element is selected from one or more of cerium, lanthanum, praseodymium, erbium and samarium.
[0047] In a specific embodiment of the present disclosure, based on the dry weight of the catalyst, the content of the modified TiO2-based carrier is 91.0-96.0% by weight, the content of the first active component is 3.0-6.0% by weight, and the content of the second active component is 1.0-3.0% by weight; wherein the content of the modified TiO2-based carrier is calculated based on the amount of TiO2, the content of the first active component is calculated based on the total amount of rare earth metal element oxides, and the content of the second active component is calculated based on the total amount of vanadium, molybdenum, antimony, niobium and tin element oxides.
[0048] In the present disclosure, by adding rare earth metal elements, the oxygen storage capacity of the catalyst can be improved, the active oxygen species and oxygen vacancies on the catalyst surface can be increased, and it is beneficial to convert NO to NO3 at low temperature. - The use of the second active component can increase the acidity of the catalyst.
[0049] In a specific embodiment of the present disclosure, the modified TiO2-based carrier is a TiO2-based carrier modified by an acid modifier; the modified TiO2-based carrier contains TiO2, and optionally WO3 and / or SiO2; the acid modifier is selected from organic acids and / or inorganic acids.
[0050] In the present disclosure, a TiO2-based carrier modified with an acid modifier is used to increase the surface acidity of the carrier, which is beneficial to improving the basic activity of the porous catalyst. The "basic activity" refers to the NH3 and NO adsorption of the catalyst. x catalytic reaction activity.
[0051] In a specific embodiment of the present disclosure, the modified TiO2-based carrier is a porous material, and the porous material contains macropores, mesopores and micropores; the specific surface area of the modified TiO2-based carrier is 50 to 90 m 2 / g, preferably 60 to 90 m 2 / g; pore volume is 0.3~0.6cm 3 / g, preferably 0.4 to 0.5 cm 3 / g; the pore volume of the macropores accounts for 2-10% of the pore volume of the porous material; the pore volume of the mesopores accounts for 30-50% of the pore volume of the porous material, and the pore volume of the micropores accounts for 45-75% of the pore volume of the porous material. The modified TiO2-based carrier used in the present disclosure is a porous material, which may contain macropores, mesopores and micropores. The pore size of the "macropores" is greater than 50nm, and the macropores can promote the volatilization of ammonium bisulfate (ABS) deposited in the pores; the pore size of the "mesopores" is between 2 and 50nm, and the mesopores are conducive to mass transfer, and can achieve good dispersion of the first active component and the second active component of the catalyst; the pore size of the "micropores" is less than 2nm, and the micropores can increase the density of active sites.
[0052] In one embodiment of the present disclosure, the modified TiO2-based carrier further contains glass fiber.
[0053] The second aspect of the present disclosure provides a method for preparing the catalyst according to the first aspect, the method comprising the following steps:
[0054] S1, mixing a TiO2-based carrier, an acid modifier and water and performing a modification treatment at 60-80° C., and performing a first drying and a first calcination on the product after evaporation to obtain a first material;
[0055] S2, performing a second mixing, a second extrusion, a second drying and a second calcination on the first material and the molding aid to obtain a modified TiO2-based carrier;
[0056] S3, performing a third impregnation of the modified TiO2-based carrier in the first auxiliary agent, and performing a third drying of the modified TiO2-based carrier after the third impregnation to obtain a third material;
[0057] S4, performing a fourth impregnation of the third material in the second auxiliary agent, and performing a fourth drying and a fourth calcination of the third material after the fourth impregnation;
[0058] Wherein, the first auxiliary agent comprises a first active component source, and the second auxiliary agent comprises a second active component source.
[0059] In the present disclosure, in step S1, the TiO2-based carrier is modified by an acid modifier so that the carrier surface has more oxygen vacancies and acid sites. After the carrier and the acid modifier are uniformly mixed and extruded into a porous material, the first auxiliary agent and the second auxiliary agent are impregnated step by step so that the active sites are more distributed on the catalyst surface, thereby reducing the amount of active components, maintaining the high activity and low SO2 oxidation rate of the catalyst, and saving costs. The present disclosure is carried out by vacuuming and then rotary evaporation in an environment with a water bath temperature of 60 to 80°C. The acid modifier is soluble in water and exists in an ionic state. The ions of the acid modifier are fully contacted with the TiO2-based carrier by rotary evaporation, and partially enter the pores of the TiO2-based carrier, thereby increasing the amount of acid on the catalyst surface and inhibiting the polymerization of active species.
[0060] In a specific embodiment of the present disclosure, in step S1, the TiO2-based carrier is selected from one or more of titanium dioxide, titanium tungsten powder and titanium tungsten silicon powder.
[0061] In a specific embodiment of the present disclosure, the concentration of the acid modifier is 0.05 to 1.2 mol / L, preferably 0.5 to 1.0 mol / L; the acid modifier is selected from organic acid and / or inorganic acid.
[0062] In a specific embodiment of the present disclosure, the mass ratio of the TiO2-based carrier to the acid modifier is 1:(10-30).
[0063] In a specific embodiment of the present disclosure, in step S2, the molding aid includes: a lubricant, a reinforcing agent, a pore former, a binder and a pH adjuster; further, the mass ratio of the first material to the molding aid is 100: (8.5-18.0); further, the mass ratio of the first material to the lubricant is 100: (0.2-2.0), the mass ratio of the first material to the reinforcing agent is 100: (4.5-8.0), and the mass ratio of the first material to the pore former is 100: (0.8-2.0) , the mass ratio of the first material to the binder is 100:(1.0-3.0), and the mass ratio of the first material to the pH regulator is 100:(10-20); wherein the lubricant is selected from one or more of stearic acid, lactic acid and glycerol; the reinforcing agent is selected from one or more of glass fiber and / or lignin; the pore-forming agent is selected from one or more of pulp cotton, activated carbon and sesbania powder; the binder is selected from one or more of hydroxymethyl cellulose, polyvinyl alcohol and polyethylene oxide; the pH regulator is ammonia water, and the mass concentration of NH3 in the ammonia water is ≥20%.
[0064] In a specific embodiment of the present disclosure, in step S3, the first auxiliary agent is a soluble salt containing a first active component source, the first active component source contains a rare earth element, the first active component source is selected from one or more of a vanadium source, a molybdenum source, an antimony source, a niobium source and a tin source, preferably selected from one or more of cerium nitrate, lanthanum nitrate, praseodymium nitrate, samarium nitrate and erbium nitrate.
[0065] In the above embodiment, the concentration of the first auxiliary agent is 0.1 to 4.0 wt %, preferably 0.2 to 1.5 wt %.
[0066] In a specific embodiment of the present disclosure, in step S4, the second auxiliary agent is a mixture containing a second active component source, and the second active component source is selected from one or more of a molybdenum source, an antimony source, a niobium source and a tin source, and is preferably selected from one or more of ammonium heptamolybdate, antimony acetate, niobium oxalate, ammonium niobium oxalate and tin acetate.
[0067] In the above embodiment, the second auxiliary agent further contains a co-solvent and a second auxiliary agent compound, and the mixture is a water-soluble mixture, the co-solvent is monoethanolamine, the concentration of the ammonium metavanadate is 1 to 5% by weight, preferably 2 to 4% by weight; the second auxiliary agent compound is a vanadium-containing salt, preferably ammonium metavanadate; specifically, the mass ratio of the co-solvent, the second active component source and the second auxiliary agent compound is (0.5 to 0.8): (0.2 to 1.8): 1, preferably (0.6 to 0.7): (0.5 to 1): 1.
[0068] In a preferred embodiment of the present disclosure, the organic acid is selected from monobasic organic acid and / or dibasic organic acid, preferably oxalic acid and / or acetic acid; the inorganic acid is selected from tribasic inorganic acid, preferably phosphoric acid.
[0069] In a preferred embodiment of the present disclosure, in step S1, the first drying conditions include: temperature of 80-120°C, time of 12-24h; the first calcination conditions include: temperature of 200-300°C, time of 8-20h;
[0070] In step S2, the second drying conditions include: temperature of 60-80°C, time of 12-15 days, and humidity of 40-60%; the second calcination conditions include: temperature of 200-300°C, time of 20-30h;
[0071] In step S3, the temperature of the third impregnation is 10-30°C, preferably 15-25°C; the time is 7-15 minutes, preferably 10-13 minutes; the conditions of the third drying include: temperature 60-90°C, preferably 70-80°C; time 12-20 hours; preferably 14-18 hours;
[0072] In step S4, the temperature of the fourth impregnation is 60-80°C, preferably 60-70°C; the time is 5-12 min, preferably 8-10 min; the conditions of the fourth drying include: temperature of 60-90°C, preferably 70-80°C; time of 15-30 h, preferably 20-24 h; humidity of 40-60%, preferably 45-55%; the conditions of the fourth calcination include: temperature of 500-600°C, preferably 500-550°C; time of 30-50 h, preferably 35-45 h.
[0073] The third aspect of the present disclosure provides application of the catalyst described in the first aspect in flue gas denitrification.
[0074] In a specific embodiment of the present disclosure, the following steps are included: at 200-420°C, the flue gas is heated for 3000-8000 hours -1 Passing the catalyst into a stainless steel fixed bed reactor containing the catalyst at a space velocity of 1.000 rpm to contact the catalyst;
[0075] The concentration of SO2 in the flue gas is 3000-6000 mg / m 3 The concentration of nitrogen oxides is 300-500 ppm, the concentration of NH3 is 300-500 ppm, the volume concentration of O2 is 3-5%, and the volume concentration of water vapor is 8-15%.
[0076] In the present disclosure, the catalyst has high activity at low temperature, a wide temperature window, and strong adaptability to complex flue gas components. The temperature range is 180-420°C, preferably 200-380°C; the air velocity is 3000-8000h -1 , honeycomb catalyst is 3000~6000mg / m 3 Under high SO2 concentration, the denitrification efficiency exceeds 90%.
[0077] The catalyst disclosed in the present invention has a higher anti-sulfur effect and can be applied to low-temperature kilns (steel, nonferrous metals, cement, waste incineration, etc.) and coal-fired power plants involved in deep peak regulation, especially coal-fired power plants with high sulfur content in coal quality.
[0078] The present disclosure is further illustrated below by way of examples, but the present disclosure is not limited thereby.
[0079] The chemicals used in each example can be obtained through public commercial channels.
[0080] The model of the flue gas analyzer is: Thermo Scientific 42i nitrogen oxide flue gas analyzer.
[0081] The model of the ion chromatograph is Thermo Fisher ICS 2100.
[0082] The model of the fluorescence spectrometer is: Shimadzu XRF-1800 Rh radiation fluorescence spectrometer.
[0083] Example 1
[0084] (1) Preparation of the first material: the carrier is titanium dioxide and titanium tungsten powder, the ratio of titanium dioxide to titanium tungsten powder is 1:3, the acid modifier is oxalic acid solution, the concentration of oxalic acid solution is 1 mol / L, and the mass ratio of oxalic acid solution to carrier (titanium dioxide and titanium tungsten powder) is 30:1. The carrier and oxalic acid solution are simultaneously placed in an evaporating flask, and the water is evaporated in a water bath at 60°C and vacuumed. After evaporation, the powder is placed in an oven at 80°C for 18 hours and then calcined in a muffle furnace at 300°C for 10 hours.
[0085] (2) Carrier mixing: the first material obtained in step (1) and the lubricant are added into a mixer at a mass ratio of 100:2, wherein the lubricant is stearic acid and lactic acid at a mass ratio of 1:3.5; the stirring device is turned on at a stirring frequency of 50 Hz, and deionized water is added to ensure that the moisture content of the mud is 30%. The stirring frequency is adjusted to 10Hz, and reinforcing agent glass fiber is added according to the mass ratio of the first material: reinforcing agent of 100:4.5, and pore-forming agent pulp cotton is added according to the mass ratio of the first material: pore-forming agent of 100:1.7. The stirring frequency is increased to 50Hz, and pH regulator ammonia water is added according to the mass ratio of the first material: pH regulator of 100:20. The moisture content of the mud is 30%, and the pH is greater than 8; the binder is evenly added to the carrier mixed mud twice according to the mass ratio of the first material: binder of 100:3. The binder is carboxymethyl cellulose and polyoxyethylene in a mass ratio of 1:1.5. Deionized water and ammonia water with a mass concentration of 20% are used to adjust the pH and moisture content of the mud to ensure that the pH is greater than 8 and the moisture content is 27%.
[0086] (3) Carrier extrusion: The obtained carrier mud is aged for 24 hours and then filtered and extruded to obtain a porous carrier wet blank.
[0087] (4) Carrier drying: The obtained wet porous carrier was sent to a constant temperature and humidity drying chamber, the temperature was slowly raised from room temperature to 60°C, and dried at 60°C for 14 days, with the humidity maintained at 45%.
[0088] (5) Pre-calcination of the carrier: The dried porous carrier wet billet was calcined at 250°C for 25 h to obtain a specific surface area of 86 m 2 / g, pore volume is 0.52cm 3 / g of modified TiO2-based carrier.
[0089] (6) Preparation of the first auxiliary agent: Take a certain amount of cerium nitrate, add it to deionized water and stir, the concentration of the cerium nitrate solution is 0.3wt%, heat the solution to 60°C, and use it as the first auxiliary agent after the solution is completely dissolved.
[0090] (7) Preparation of the second auxiliary agent: dissolve monoethanolammonium in deionized water, add monoethanolamine, heat the solution to 60° C., add ammonium metavanadate and ammonium heptamolybdate and stir, the mass ratio of monoethanolamine: ammonium metavanadate: ammonium heptamolybdate is 0.7:1:1, the concentration of the ammonium metavanadate solution is 1.3 wt %, and the solution is used as the second auxiliary agent after it is completely dissolved.
[0091] (8) Impregnation with the first auxiliary agent: The carrier obtained in step (5) is placed in the first auxiliary agent and impregnated at 25° C. for 10 min. After impregnation, the catalyst is dried at 70° C. for 18 h.
[0092] (9) Impregnation with the second auxiliary agent: The catalyst obtained in step (8) is placed in the second auxiliary agent and impregnated at 65° C. for 10 min. After impregnation, the catalyst is sent to a constant temperature and humidity drying room, slowly raised from room temperature to 60° C., and dried at 70° C. and 45% humidity for 24 h.
[0093] (10) Calcination: The catalyst obtained in step (9) was dried in an oven at 60° C. for 12 h, and then calcined in a mesh bag kiln at 550° C. for 40 h. After cutting and hardening the ends, a high sulfur resistance and wide temperature window SCR denitration catalyst product was obtained; the denitration efficiency of the catalyst is listed in Table 1, and the SO2 / SO3 conversion rate of the catalyst is listed in Table 2.
[0094] Based on the dry weight of the catalyst, the content of the TiO2-based carrier is 92.8% by weight, the content of the first active component oxide is 5.2% by weight, and the content of the second active component oxide is 2.0% by weight.
[0095] Example 2
[0096] (1) Preparation of the first material: the carrier is titanium dioxide and titanium tungsten silicon powder, the ratio of titanium tungsten powder to titanium tungsten silicon powder is 5:1, the acid modifier is acetic acid solution, the concentration of acetic acid solution is 1 mol / L, the mass ratio of carbonic acid solution to carrier (titanium dioxide and titanium tungsten powder) is 25:1, the carrier and the carbonic acid solution are simultaneously put into an evaporating flask, the water is evaporated in a water bath at 60°C and vacuumed, and after evaporation, the powder is placed in an oven at 80°C for 16 hours and calcined in a muffle furnace at 300°C for 10 hours.
[0097] (2) Carrier mixing: the first material obtained in step (1) and the lubricant are added into a mixer at a mass ratio of the first material to the lubricant of 100:1.5, wherein the lubricant is stearic acid and lactic acid at a mass ratio of 1:4.2; the stirring device is turned on at a stirring frequency of 50 Hz, and deionized water is added to ensure that the moisture content of the mud is 32%. The stirring frequency is adjusted to 10Hz, and reinforcing agent glass fiber is added according to the mass ratio of the first material: reinforcing agent of 100:5.2, and pore-forming agent pulp cotton is added according to the mass ratio of the first material: pore-forming agent of 100:2.0. The stirring frequency is increased to 50Hz, and pH regulator ammonia water is added according to the mass ratio of the first material: pH regulator of 100:20. The moisture content of the mud is 32%, and the pH is greater than 8; the binder is evenly added to the carrier mixed mud twice according to the mass ratio of the first material: binder of 100:2.2. The binder is carboxymethyl cellulose and polyoxyethylene in a mass ratio of 1:2.1. Deionized water and ammonia water with a mass concentration of 20% are used to adjust the pH and moisture content of the mud to ensure that the pH is greater than 8 and the moisture content is 29%.
[0098] (3) Carrier extrusion: The obtained carrier mud is aged for 24 hours and then filtered and extruded to obtain a porous carrier wet blank.
[0099] (4) Carrier drying: The obtained wet porous carrier was sent to a constant temperature and humidity drying chamber, slowly heated from room temperature to 60°C, and dried at 60°C for 14 days, with the humidity maintained at 60%; the specific surface area was 78 m 2 / g, pore volume is 0.45cm 3 / g of modified TiO2-based carrier.
[0100] (5) Pre-calcination of the carrier: The dried wet porous carrier was calcined at 300°C for 30 h.
[0101] (6) Preparation of the first auxiliary agent: Take a certain amount of lanthanum nitrate, add it to deionized water and stir, the concentration of the lanthanum nitrate solution is 1.0 wt%, heat the solution to 60° C., and use it as the first auxiliary agent after the solution is completely dissolved.
[0102] (7) Preparation of the second auxiliary agent: monoethanolammonium was dissolved in deionized water, and ammonium metavanadate and antimony acetate were added. The mass ratio of monoethanolamine: ammonium metavanadate: antimony acetate was 0.8:1:1.5, and the concentration of the ammonium metavanadate solution was 2.7 wt %. The solution was heated to 60° C. and stirred. After the solution was completely dissolved, it was used as the second auxiliary agent.
[0103] (8) Impregnation with the first auxiliary agent: The carrier obtained in step (5) was placed in the first auxiliary agent and impregnated at 20° C. for 13 min. After impregnation, the catalyst was dried at 80° C. for 16 h.
[0104] (9) Impregnation with the second auxiliary agent: The catalyst obtained in step (8) is placed in the second auxiliary agent and impregnated at 60° C. for 10 min. After impregnation, the catalyst is sent to a constant temperature and humidity drying room, slowly raised from room temperature to 80° C., and dried at 80° C. and 55% humidity for 20 h.
[0105] (10) Calcination: The catalyst obtained in step (9) was dried in an oven at 60° C. for 12 h, and then calcined in a mesh bag kiln at 500° C. for 50 h. After cutting and hardening the ends, a high sulfur resistance and wide temperature window SCR denitration catalyst product was obtained. The denitration efficiency of the catalyst is listed in Table 1, and the SO2 / SO3 conversion rate of the catalyst is listed in Table 2.
[0106] Based on the dry weight of the catalyst, the content of the TiO2-based carrier is 94.7% by weight, the content of the first active component oxide is 3.1% by weight, and the content of the second active component oxide is 2.2% by weight.
[0107] Example 3
[0108] The method for preparing the catalyst in this embodiment is the same as that in embodiment 1, except that the second auxiliary agent is prepared by dissolving monoethanolammonium in deionized water, adding ammonium metavanadate and tin acetate, the mass ratio of monoethanolamine: ammonium metavanadate: tin acetate is 0.6: 0.7: 1.0, the concentration of the ammonium metavanadate solution is 3 wt %, and the solution is heated to 65° C. and stirred, and the solution is used as the second auxiliary agent after it is completely dissolved;
[0109] The denitration efficiency of the catalyst is listed in Table 1, and the SO2 / SO3 conversion rate of the catalyst is listed in Table 2;
[0110] Based on the dry weight of the catalyst, the content of the TiO2-based carrier is 93.2% by weight, the content of the first active component oxide is 5.1% by weight, and the content of the second active component oxide is 1.7% by weight.
[0111] Example 4
[0112] The method for preparing the catalyst in this embodiment is the same as that in embodiment 1, except that: in step (6), the first auxiliary agent is prepared by taking a certain amount of cerium nitrate, adding it to deionized water and stirring, wherein the concentration of the cerium nitrate solution is 0.1wt%, and heating the solution to 60°C, and using the solution as the first auxiliary agent after it is completely dissolved;
[0113] The denitration efficiency of the catalyst is listed in Table 1, and the SO2 / SO3 conversion rate of the catalyst is listed in Table 2;
[0114] Based on the dry weight of the catalyst, the content of the TiO2-based carrier is 94.2% by weight, the content of the first active component oxide is 3.6% by weight, and the content of the second active component oxide is 2.2% by weight.
[0115] Example 5
[0116] The method for preparing the catalyst in this embodiment is the same as that in embodiment 1, except that: Preparation of the second auxiliary agent: dissolve monoethanolammonium in deionized water, add ammonium metavanadate and ammonium heptamolybdate, the mass ratio of monoethanolamine: ammonium metavanadate: ammonium heptamolybdate is 0.5:0.2:1, the concentration of the ammonium metavanadate solution is 1.3wt%, heat the solution to 60°C, stir, and use the solution as the second auxiliary agent after it is completely dissolved;
[0117] The denitration efficiency of the catalyst is listed in Table 1, and the SO2 / SO3 conversion rate of the catalyst is listed in Table 2;
[0118] Based on the dry weight of the catalyst, the content of the TiO2-based carrier is 94.0% by weight, the content of the first active component oxide is 4.8% by weight, and the content of the second active component oxide is 1.2% by weight.
[0119] Example 6
[0120] The method for preparing the catalyst in this comparative example is the same as that in Example 1, except that: the immersion time of the carrier in the first auxiliary agent solution in step (8) is 8 minutes, and the immersion time of the carrier in the second auxiliary agent solution in step (9) is 6 minutes; the denitration efficiency of the catalyst is listed in Table 1, and the SO2 / SO3 conversion rate of the catalyst is listed in Table 2;
[0121] Based on the dry weight of the catalyst, the content of the TiO2-based carrier is 94.1% by weight, the content of the first active component oxide is 4.7% by weight, and the content of the second active component oxide is 1.2% by weight.
[0122] Comparative Example 1
[0123] The method for preparing the catalyst in this comparative example is the same as that in Example 1, except that a carrier which has not been modified by acid is used;
[0124] The denitration efficiency of the catalyst is listed in Table 1, and the SO2 / SO3 conversion rate of the catalyst is listed in Table 2;
[0125] Based on the dry weight of the catalyst, the content of the TiO2-based carrier is 92.8% by weight, the content of the first active component oxide is 4.9% by weight, and the content of the second active component oxide is 2.3% by weight.
[0126] Comparative Example 2
[0127] The method for preparing the catalyst in this comparative example is the same as that in Example 1, except that the first auxiliary agent and the second auxiliary agent are both added during the carrier mixing process in step (2), and steps (5), (8), and (9) are omitted; the denitration efficiency of the catalyst is listed in Table 1, and the SO2 / SO3 conversion rate of the catalyst is listed in Table 2;
[0128] Based on the dry weight of the catalyst, the content of the TiO2-based carrier is 92.8% by weight, the content of the first active component oxide is 5.2% by weight, and the content of the second active component oxide is 2.0% by weight.
[0129] Comparative Example 3
[0130] The method for preparing the catalyst in this comparative example is the same as that in Example 1, except that: in step (1), the carrier and the carbonic acid solution are simultaneously placed in an evaporating flask and ultrasonicated for 60 min at a temperature of 60° C. The denitration efficiency of the catalyst is listed in Table 1, and the SO2 / SO3 conversion rate of the catalyst is listed in Table 2;
[0131] Based on the dry weight of the catalyst, the content of the TiO2-based carrier is 92 weight %, the content of the first active component oxide is 4 weight %, and the content of the second active component oxide is 4 weight %.
[0132] Comparative Example 4
[0133] The method for preparing the catalyst in this comparative example is the same as that in Example 1, except that the first auxiliary agent and the second auxiliary agent are mixed and then the carrier is impregnated for 10 minutes; the denitration efficiency of the catalyst is listed in Table 1, and the SO2 / SO3 conversion rate of the catalyst is listed in Table 2;
[0134] Based on the dry weight of the catalyst, the content of the TiO2-based carrier is 94.5% by weight, the content of the first active component oxide is 4.3% by weight, and the content of the second active component oxide is 1.2% by weight.
[0135] Test Example 1
[0136] Catalyst performance test: an experimental platform was built, the catalyst prepared as above was selected and placed in a stainless steel fixed bed reactor. After stabilization for 2 h in the temperature range of 200-380°C, the denitrification efficiency at each temperature point was tested. The denitrification efficiency was characterized by the NO conversion rate. The results are shown in Table 1.
[0137] Pass simulated flue gas (SO2 = 3000-6000mg / m 3 , NO x =NH3=300ppm, O2=3%, H2O=8%, N2 as balance gas), space velocity=6000h -1 The catalyst inlet and outlet NO was tested using a Thermo NOx flue gas analyzer. x concentration.
[0138] NO conversion rate:
[0139]
[0140] Where: NO at the reactor inlet x Concentration, in ppm; NO at the reactor outlet x Concentration, in ppm.
[0141] Test Example 2
[0142] SO2 / SO3 conversion rate test: Sampling is done at the inlet of the SCR reactor, and the inlet SO2 content is measured using an infrared flue gas analyzer. The average value is recorded as S1 in mg / Nm 3 . Samples were collected at the inlet and outlet of the SCR reactor, and the inlet and outlet SO3 were collected by temperature-controlled condensation. The inlet and outlet SO3 content was determined by ion chromatography, and the average value was taken and recorded as S2 in mg / Nm 3 The SO2 / SO3 conversion rate α of the catalyst was calculated based on this, and the results are shown in Table 2.
[0143]
[0144] Test Example 3
[0145] Characterization of acid sites on the catalyst surface: NH3-TPD characterization test was carried out on an Auto Chem II 2920 adsorption tester (Micromeritics, USA). The distribution of acid sites on the catalyst surface was inferred based on the relationship curve between temperature and the desorption amount of surface adsorbed NH3.
[0146] like Figure 1 As shown in the figure, the desorption peak at 150-300°C represents weak acid sites, and the desorption peak at 300-500°C represents medium-strong acid sites. The amount of NH3 desorption is positively correlated with the amount of acid in this temperature range. Under the operating condition of 200-380°C, weak acid sites and medium-strong acid sites play a major role. It can be seen that compared with Comparative Example 1, the weak acid sites and medium-strong acid sites on the catalyst surface of Example 1 are enhanced.
[0147] Table 1 Denitrification efficiency of catalyst (%)
[0148]
[0149] Table 2 SO2 / SO3 conversion rate of catalyst (%)
[0150] First Test Second test Third test average value Example 1 0.13 0.16 0.15 0.15 Example 2 0.15 0.16 0.16 0.16 Example 3 0.21 0.18 0.17 0.19 Example 4 0.16 0.17 0.14 0.16 Example 5 0.22 0.25 0.21 0.23 Example 6 0.13 0.14 0.12 0.13 Comparative Example 1 0.28 0.3 0.27 0.28 Comparative Example 2 0.51 0.48 0.52 0.50 Comparative Example 3 0.18 0.16 0.20 0.18 Comparative Example 4 0.26 0.29 0.25 0.27
[0151] It can be seen from Tables 1 and 2 that the catalysts prepared in Examples 1 to 6 of the present disclosure have better denitration efficiency and lower SO2 / SO3 conversion rate than the catalysts prepared in Comparative Examples 1 to 4. This indicates that the catalysts of the present disclosure have lower SO2 / SO3 conversion rate and higher denitration efficiency in a wide temperature window range of 180-420°C, preferably 200-380°C.
[0152] Among them, (1) the denitration efficiency of the catalyst obtained in Example 1 of the present disclosure is higher than that of Comparative Example 1, and the SO2 / SO3 conversion rate is lower than that of Comparative Example 1, indicating the beneficial effect of the TiO2-based carrier modified by the acid modifier;
[0153] (2) The denitration efficiency of the catalyst obtained in Example 1 of the present disclosure is higher than that in Comparative Example 2, and the SO2 / SO3 conversion rate is lower than that in Comparative Example 2, indicating the beneficial effect of first extruding the porous material and then impregnating the first auxiliary agent and the second auxiliary agent in steps;
[0154] (3) The denitration efficiency of the catalyst obtained in Example 1 of the present disclosure is higher than that in Comparative Example 3, and the SO2 / SO3 conversion rate is lower than that in Comparative Example 3, indicating the beneficial effect of acid modification of the TiO2-based carrier by vacuum rotary evaporation in a water bath temperature environment of 60-80°C;
[0155] (4) The denitration efficiency of the catalyst obtained in Example 1 of the present disclosure is higher than that of Comparative Example 4, and the SO2 / SO3 conversion rate is lower than that of Comparative Example 4, indicating the beneficial effect of step-by-step impregnation of the first auxiliary agent and the second auxiliary agent.
[0156] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0157] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0158] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A high sulfur resistance and wide temperature window denitrification catalyst, It is characterized in that The catalyst has an acidic site, and the catalyst contains modified TiO 2 The base carrier, the first active component and the second active component, wherein the first active component and the second active component are distributed on the modified TiO 2 an outer surface of a base carrier; The first active component contains an oxide of a rare earth metal element, and the second active component is selected from one or more oxides of vanadium, molybdenum, antimony, niobium and tin; Based on the dry weight of the catalyst, the modified TiO 2 The content of the base carrier is 91.0-96.0% by weight, the content of the first active component is 3.0-6.0% by weight, and the content of the second active component is 1.0-3.0% by weight; Wherein, the modified TiO 2 The content of the base carrier is TiO 2 The content of the first active component is calculated based on the total amount of oxides of rare earth metal elements, and the content of the second active component is calculated based on the total amount of oxides of vanadium, molybdenum, antimony, niobium and tin elements.
2. The catalyst according to claim 1, in, The modified TiO 2 The outer surface of the base carrier is coated with a first active component layer and a second active component layer in sequence; The modified TiO 2 The base support is TiO modified by an acid modifier. 2 Base carrier; The modified TiO 2 The base carrier contains TiO 2 , and optional WO 3 and / or SiO 2 ; The acid modifier is selected from organic acids and / or inorganic acids.
3. The catalyst according to claim 2, in, The modified TiO 2 The base carrier is a porous material, and the porous material contains macropores, mesopores and micropores; the modified TiO 2 The specific surface area of the base carrier is 50 to 90 m 2 / g, preferably 60 to 90 m 2 / g; pore volume is 0.3~0.6cm 3 / g, preferably 0.4 to 0.5 cm 3 / g; the pore volume of the macropores accounts for 2-10% of the pore volume of the porous material; the pore volume of the mesopores accounts for 30-50% of the pore volume of the porous material, and the pore volume of the micropores accounts for 45-75% of the pore volume of the porous material.
4. The catalyst according to claim 1, in, The rare earth metal element is selected from one or more of cerium, lanthanum, praseodymium, erbium and samarium.
5. A method for preparing the catalyst according to any one of claims 1 to 4, It is characterized in that The method comprises the following steps: S1, TiO 2 The base carrier, the acid modifier and water are mixed and subjected to modification treatment at 60-80° C., and the product after evaporation is subjected to first drying and first roasting to obtain a first material; S2, performing a second mixing, a second extrusion, a second drying and a second calcination on the first material and the molding aid to obtain a modified TiO 2 Base carrier; S3, the modified TiO 2 The base support is impregnated in the first auxiliary agent for the third time, and the modified TiO 2 The base carrier is subjected to a third drying to obtain a third material; S4, performing a fourth impregnation of the third material in the second auxiliary agent, and performing a fourth drying and a fourth calcination of the third material after the fourth impregnation; Wherein, the first auxiliary agent comprises a first active component source, and the second auxiliary agent comprises a second active component source.
6. The method according to claim 5, in, In step S1, the TiO 2 The base carrier is selected from one or more of titanium dioxide, titanium tungsten powder and titanium tungsten silicon powder; The concentration of the acid modifier is 0.05 to 1.2 mol / L, preferably 0.5 to 1.0 mol / L; the acid modifier is selected from organic acid and / or inorganic acid; The TiO 2 The mass ratio of the base carrier to the acid modifier is 1:(10-30); In step S2, the molding aids include: a lubricant, a reinforcing agent, a pore-forming agent, a binder and a pH adjuster; The lubricant is selected from one or more of stearic acid, lactic acid and glycerol; The reinforcing agent is selected from glass fiber and / or lignin; The pore-forming agent is selected from one or more of pulp cotton, activated carbon and sesbania powder; The binder is selected from one or more of hydroxymethyl cellulose, polyvinyl alcohol and polyethylene oxide; The pH regulator is aqueous ammonia, wherein NH 3 The mass concentration of ≥20%; In step S3, the first auxiliary agent is a soluble salt containing a first active component source, the first active component source contains a rare earth element, the first active component source is selected from one or more of a vanadium source, a molybdenum source, an antimony source, a niobium source and a tin source, preferably selected from one or more of cerium nitrate, lanthanum nitrate, praseodymium nitrate, samarium nitrate and erbium nitrate; In step S4, the second auxiliary agent is a mixture containing a second active component source, and the second active component source is selected from one or more of a molybdenum source, an antimony source, a niobium source and a tin source, preferably selected from one or more of ammonium heptamolybdate, antimony acetate, niobium oxalate, ammonium niobium oxalate and tin acetate.
7. The method according to claim 6, in, The organic acid is selected from monobasic organic acids and / or dibasic organic acids, preferably oxalic acid and / or acetic acid; The inorganic acid is selected from ternary inorganic acids, preferably phosphoric acid; The concentration of the first auxiliary agent is 0.1 to 4.0% by weight, preferably 0.2 to 1.5% by weight; The second auxiliary agent further contains a co-solvent and a second auxiliary agent compound, and the mass ratio of the co-solvent, the second active component source and the second auxiliary agent compound is (0.5-0.8):(0.2-1.8):1, preferably (0.6-0.7):(0.5-1):
1.
8. The method according to claim 5, It is characterized in that In step S1, the first drying conditions include: temperature of 80 to 120°C and time of 12 to 24 hours; The first calcination conditions include: a temperature of 200 to 300° C. and a time of 8 to 20 hours; In step S2, the second drying conditions include: temperature of 60-80°C, time of 12-15 days, and humidity of 40-60%; The second calcination conditions include: a temperature of 200 to 300° C. and a time of 20 to 30 hours; In step S3, the temperature of the third immersion is 10-30°C, preferably 15-25°C; the time is 7-15 minutes, preferably 10-13 minutes; The conditions of the third drying include: a temperature of 60 to 90°C, preferably 70 to 80°C; a time of 12 to 20 hours, preferably 14 to 18 hours; In step S4, the temperature of the fourth dipping is 60-80°C, preferably 60-70°C; the time is 5-12 minutes, preferably 8-10 minutes; The fourth drying conditions include: temperature of 60-90°C, preferably 70-80°C; time of 15-30h, preferably 20-24h; humidity of 40-60%, preferably 45-55%; The conditions for the fourth calcination include: a temperature of 500 to 600° C., preferably 500 to 550° C.; and a time of 30 to 50 hours, preferably 35 to 45 hours.
9. Use of the catalyst according to any one of claims 1 to 4 in flue gas denitration.
10. The use according to claim 9, It is characterized in that The following steps are involved: At 200-420℃, the flue gas is heated for 3000-8000h -1 Passing the catalyst into a fixed bed reactor at a space velocity of 1.5 wt %. The SO in the flue gas 2 The concentration is 3000~6000mg / m 3 , the concentration of nitrogen oxides is 300-500ppm, NH 3 The concentration of O is 300~500ppm, 2 The volume concentration of carbon dioxide is 3-5%, and the volume concentration of water vapor is 8-15%.
Citation Information
Cited By
Composite filter material for preventing bag from being burnt by ammonium bisulfate as well as preparation method and application of composite filter material
CN120171144A
